Meat procurement strategy from the Neolithic to the Bronze Age in the Guanzhong region of Shaanxi Province, China - Hu, Qingbo; Dong, Ningning; Hu, Songmei; Qin, Xiaoli; Yuan, Jing (Frontiers in Earth Science, 2023)
Meat procurement strategies, displaying a great variety world-widely, are ideal for examining how geography and culture shape the subsistence. We collate zooarchaeological data from 26 Neolithic and Bronze Age sites/ locales in the Guanzhong region (Shaanxi Province, China), a key region of early Chinese civilization, to demonstrate the changing process of meat procurement and its associations with environmental, demographic and societal factors. Comparing the proportion of the domesticates versus wild animals, along with the proportion of the domesticated pigs versus bovids (i.e. sheep, goat, and cattle), we summarize three characteristics of the meat procurement strategy at Guanzhong. Firstly, the changing pattern of meat procurement did not follow a linear progression of shifting subsistence from hunting to husbandry, albeit involving acceleration and regression from the pre-Yangshao period to the Western Zhou dynasty. Secondly, contrasting meat procurement strategies might have been employed between central settlements and lower-ranking settlements. Thirdly, an increasing importance of domesticated bovids was evident during the pre-Zhou and Western Zhou periods. We therefore argue population size and societal form might have shaped meat procurement strategies, in addition to natural environments. Subsistence, in turn, also lays the economic foundation for social development. It was not until the pre-Zhou and Western Zhou periods, when a more stable meat procurement strategy 2 involving utilizing a variety of the domesticates was pervasively employed in this region, that Guanzhong had gradually gained its prominence in Chinese civilization.